VARIOUS APPROACHES AND ACTIVITIES OF TEACHING ANTONYMS IN MODERN ENGLISH LINGUISTICS - Safarova , Lobar; Khamrayeva, M.G (Innovative Development in Educational Activities, 2023)
The article provides information about antonyms, its types, and how to teach them through interactive methods of teaching to school students during the English class, which leads to improve their critical thinking, fast response and active participation as well as enhance their outlook. Furthermore, the article contains some thoughts and approaches expressed by famous linguists.